Stik Kelor: Inovasi Produk Olahan Daun Kelor dalam Upaya Meningkatkan Perekonomian Masyarakat Desa Branta Tinggi Kec. Tlanakan Kab. Pamekasan - Ria kasanova; Sholeh Rachmatullah; Sri Widjajanti; Mohammad Rudiyanto (Fakultas Sains dan Teknologi, Universitas Jambi, 2021)
Branta Tinggi Village is located in Tlanakan District, Pamekasan Regency, this village consists of three hamlets/villages and about 6,889 people. With a population of 2906 men and 3,733 women, the people of Branta Tinggi Village rely on the fisheries, agriculture and entrepreneurship sectors. However, the people of this high branta village do not have the skills to utilize the moringa plant (Moringa oleifera). which grows a lot in people's yards into processed products that have high economic value, this Moringa leaf is a plant that has various economic benefits and this Moringa plant grows a lot in the yards of the Branta Tinggi village community and Moringa can be used as one of the mainstay commodities to be developed more good for supporting the economy of the community. There are several methods that will be implemented in this service, including direct field observations and approaches to education, practice and mentoring. To achieve maximum results in the innovation of Moringa leaves into processed products, the efforts that will be made by the team are to provide seminars to partners on processing Moringa leaf innovations, conduct simulations and practices of processing fresh Moringa leaves into Moringa stick products, conduct training on packaging and management. Good marketing is a way to compete without having to kill competitors related to processed products of Moringa leaf sticks and other snack foods with digital market systems or manual marketing.